2021
DOI: 10.1021/acsami.1c16738
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Peptides and Hyaluronic Acid-Based Injectable Composite Hydrogels for Sustained Drug Release and Chronic Diabetic Wound Healing

Abstract: Peptide hydrogels are widely used for biomedical applications owing to their good biocompatibility and unique advantages in terms of amino acid-based structures and functions. However, the exploration of the peptide/saccharide composite hydrogels as potential biomaterials for chronic diabetic wound healing is still limited. Herein, hyaluronic acid (HA) was incorporated into diphenylalanine (FF) conjugated with different aromatic moieties by a one-pot reaction. Our results showed that the dipeptide derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…As expected, the thixotropic property endowed the gel to be simply injected through a syringe and then returned to its gelled stated after injection. Deng et al also demonstrated the self-healing behavior of a composite hydrogel made of a series of aromatic-capped group (benzene, naphthalene, 2-anthracene, 9-anthracenemethoxycarbonyl, and 1-pyrene), with the most-studied being diphenylalanine (PhePhe) unit and a biocompatible natural polysaccharide, hyaluronic acid (HA) [ 180 ]. Out of these composite hydrogels, the N-PhePhe/HA gel showed better injectability and self-healing ability.…”
Section: Thixotropic Composite Hydrogelmentioning
confidence: 99%
“…As expected, the thixotropic property endowed the gel to be simply injected through a syringe and then returned to its gelled stated after injection. Deng et al also demonstrated the self-healing behavior of a composite hydrogel made of a series of aromatic-capped group (benzene, naphthalene, 2-anthracene, 9-anthracenemethoxycarbonyl, and 1-pyrene), with the most-studied being diphenylalanine (PhePhe) unit and a biocompatible natural polysaccharide, hyaluronic acid (HA) [ 180 ]. Out of these composite hydrogels, the N-PhePhe/HA gel showed better injectability and self-healing ability.…”
Section: Thixotropic Composite Hydrogelmentioning
confidence: 99%
“…For instance, Li et al reported dipeptide derivatives (diphenylalanine, FF) modified with aromatic moieties self‐assembled into composite hydrogels in the presence of HA and curcumin. [ 155 ] The prepared curcumin‐loaded N–FF (naphthalene–modified FF)/HA composite hydrogels not only showed improved self‐healing properties and good biocompatibility but also had sustained drug release effects at a slow rate within a long period. The diabetic mice wound healing results showed that the wound area decreased significantly in N–FF/HA/Cur hydrogels group when compared with blank N–FF/HA‐treated group on day 14 (5.48% ± 2.06% in N–FF/HA/Cur group vs. 11.71% ± 2.54% in N–FF/HA group, * P < 0.05).…”
Section: Hyaluronic Acid‐based Hydrogels In Wound Dressingmentioning
confidence: 99%
“…The HA donates biocompatibility and enhanced mechanical properties to the composite hydrogel. [ 165 ] a Phosphatase, b esterase, c diphenylalanine, d hyaluronic acid. …”
Section: Nanobioconjugatesmentioning
confidence: 99%